Acute Otomastoiditis in a Preterm Newborn: A Case Report - Araújo, Ozanil Cursino; Tatiane Maria de Miranda, Tatiane Maria de Miranda; Gomez, Dafne Barcala Coutinho do Amaral; De Biase, Francisco; Alves, João Guilherme Bezerra (Brazilian Journal of Case Reports, 2025)
Otomastoiditis is a rare but severe complication of acute otitis media, particularly in infants under six months of age, where classical symptoms may be absent, leading to diagnostic and therapeutic challenges. We present the case of a preterm infant (gestational age: 31 weeks) diagnosed with acute otomastoiditis complicated by a subperiosteal abscess. The infant was initially admitted to the Kangaroo Unit due to prematurity. On the 20th day of life, the newborn presented with apnea and cyanosis. On the 21st day of hospitalization, she developed a left retroauricular swelling with erythema and tenderness. Bedside ultrasound revealed a fluid-filled area with a breach in the outer bone layer, confirming the diagnosis of a subperiosteal abscess secondary to otomastoiditis. CT findings were mastoid opacification, cortical bone erosion and subperiosteal abscess. A multidisciplinary approach was employed, including otorhinolaryngology consultation, imaging studies (cranial computed tomography), and surgical intervention. The patient underwent abscess drainage, followed by mastoidectomy and placement of a ventilation tube. Cultures yielded Staphylococcus aureus, guiding continued treatment with oxacillin for 21 days. The infant showed progressive clinical improvement and was discharged on the 41st day of hospitalization. This case underscores the importance of prompt identification of atypical signs of otomastoiditis in preterm infants and highlights the crucial role of surgical and targeted antibiotic therapy.